2006
DOI: 10.1007/s10584-006-9051-4
|View full text |Cite
|
Sign up to set email alerts
|

Going to the Extremes

Abstract: Projections of changes in climate extremes are critical to assessing the potential impacts of climate change on human and natural systems. Modeling advances now provide the opportunity of utilizing global general circulation models (GCMs) for projections of extreme temperature and precipitation indicators. We analyze historical and future simulations of ten such indicators as derived from an ensemble of 9 GCMs contributing to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
349
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 982 publications
(390 citation statements)
references
References 53 publications
33
349
0
8
Order By: Relevance
“…It refers to both a shift in mean climatic conditions (e.g. temperature and precipitation) and an increase in the frequency and severity of weather extremes (Tebaldi et al 2006;Eitzinger et al 2013;Porter et al 2014;Mandryk et al 2017). Economic activities prompted by industrial revolution have been contributed to climate change through increasing GHGs emission (IPCC 2007a).…”
Section: Agriculture and Climate Change: A Two-way Relationshipmentioning
confidence: 99%
“…It refers to both a shift in mean climatic conditions (e.g. temperature and precipitation) and an increase in the frequency and severity of weather extremes (Tebaldi et al 2006;Eitzinger et al 2013;Porter et al 2014;Mandryk et al 2017). Economic activities prompted by industrial revolution have been contributed to climate change through increasing GHGs emission (IPCC 2007a).…”
Section: Agriculture and Climate Change: A Two-way Relationshipmentioning
confidence: 99%
“…In addition, future climate simulations generally project increases in the greatest precipitation events over northwestern and northeastern US (Meehl et al 2005). However, there are large uncertainties related to GCMs, RCMs and statistical downscaling methods, and by natural variability of the climate (Tebaldi et al 2006;Kharin et al 2007;Kyselỳ and Beranová 2009;Kenyon and Hegerl 2010;Orlowsky and Seneviratne 2012).…”
mentioning
confidence: 99%
“…Modelling groups have also now taken a similar approach through the Joint Scientific Committee (JSC)/CLIVAR Working Group on Coupled Models so that observations and model output can be compared consistently. The study by Tebaldi et al (2006) was the first to use the multi-model approach to assess potential future changes in climate extremes showing that the twenty-first century would bring global changes in temperature extremes consistent with a warming climate. While that study also showed that global changes in precipitation extremes were consistent with a wetter world with greater precipitation intensity, the consensus and significance amongst the models were weaker when regional patterns were considered.…”
mentioning
confidence: 99%